Using reheating of baked products to prolong their freshness - Bilyk, Olena; Bogachov, Iurii; Bondarenko, Yulia; Fain, Albina; Bilokhatniuk, Volodymyr (Technology audit and production reserves, 2025)
The object of research is the technological process of reheating bakery products after cooling. The study is devoted to the development of technological methods for extending the freshness of bakery products to reduce bread waste into the environment. Traditional methods for extending the freshness of bakery products require the use of high-quality raw materials, packaging materials, food additives, non-traditional raw materials, and the use of rational methods of storing finished products which in turn leads to an increase in the cost of products. This work considers the possibility of using reheating of bakery products after a certain storage period, which may allow them to be produced with an extended shelf life without the use of additional ingredients, food additives, and technological equipment. It was established that to slow down the staling process, the optimal temperature for reheating of bakery products weighing 0.060 kg is heating the finished products to 75 °C. It was established that reheating reduces the friability of products compared to the control by 27.0 % under the condition of storage for 48 hours. Along with this, it was found that the water binding of the crumb of products after reheating also decreases during storage, but this decrease after 48 h of storage compared to the control is 15.5 % greater, which indicates a slowdown in the aging of the hydrocolloids of the products. It was found that the lightness (color L∗) of the bakery product after reheating significantly decreased from 66.81 to 59.38, which indicates darkening due to the Maillard reaction. Due to reheating, the formation of the subcrust layer of bakery products occurs more slowly and the crust to crumb ratio is 57.5 % less compared to the control. Thus, the use of reheating is an effective technological measure for extending the freshness of bakery products.